A phase III, randomized, non-inferiority trial to assess the efficacy and safety of dihydroartemisinin-piperaquine in comparison with artesunate- mefloquine in patients with uncomplicated Plasmodium falciparum Malaria in Southern Laos - Mayfong Mayxay (2018)
We conducted an open, randomized clinical trial of oral dihydroartemisinin-piperaquine (DP) versus artesunate-mefloquine (AM) in 300 patients in Laos with uncomplicated Plasmodium falciparum malaria as part of a multicentre study in Asia. Survival analysis and adjustment for re-infection showed that the 63-day cure rates (95% confidence interval [CI]) were 100% for AM and 99.5% (96.4-99.8%) for DP. The 63-day cure rates per protocol were 99% (97 of 98) for AM and 99.5% (196 of 197) for DP (P = 0.55).The difference (AM minus DP) in cure rates (95% CI) was -0.5% (-5.1 to 2.0%), which is within the 5% non-inferiority margin. The median fever and parasite clearance times were also similar for AM and DP. The proportion of patients with at least one recorded potential adverse event was significantly higher in the AM group (38 of 87,44%) than in the DP group (57 of 182, 31%) (relative risk = 0.6, 95% CI = 0.4-0.9; P = 0.04). Dihydroartemisinin-piperaquine is not inferior to AM in the treatment of uncomplicated P. falciparum malaria in Laos and is associated with fewer adverse effects. The results of this study were similar to those of the larger multicentre study. Copyright © 2010 by The American Society of Tropical Medicine and Hygiene.